Proteomic Identification and Time-Course Monitoring of Secreted Proteins During Expansion of Human Mesenchymal Stem/Stromal in Stirred-Tank Bioreactor - Mizukami, Amanda; Thomé, Carolina Hassibe; Ferreira, Germano Aguiar; Lanfredi, Guilherme Pauperio; Covas, Dimas Tadeu; Pitteri, Sharon J.; Swiech, Kamilla; Faça, Vitor Marcel (Frontiers in Bioengineering and Biotechnology, 2019)
The therapeutic potential of mesenchymal stem/stromal cells (MSC) is widely recognized for the treatment of several diseases, including acute graft-versus-host disease (GVHD), hematological malignancies, cardiovascular, bone and cartilage diseases. More recently, this therapeutic efficacy has been attributed to the bioactive molecules that these cells secrete (secretome), now being referred as medicinal signaling cells. This fact raises the opportunity of therapeutically using MSC-derived soluble factors rather than cells themselves, enabling their translation into the clinic. Indeed, many clinical trials are now studying the effects of MSC-secretome in the context of cell-free therapy. MSC secretome profile varies between donors, source, and culture conditions, making their therapeutic use very challenging. Therefore, identifying these soluble proteins and evaluating their production in a reproducible and scalable manner is even more relevant. In this work, we analyzed the global profile of proteins secreted by umbilical cord matrix (UCM) derived-MSC in static conditions by using mass spectrometry, enabling the identification of thousands of proteins. Afterwards, relevant proteins were chosen and monitored in the supernatant of a fully-controllable, closed and scalable system (bioreactor) by using multiple reaction monitoring (MRM) technique in a time-dependent manner. The results showed that the majority of interesting proteins were enriched through time in culture, withthe last day of culture being the ideal time for supernatant collection. The use of this regenerative “soup”, which is frequently discarded, could represent a step toward a safe, robust and reproducible cell-free product to be used in the medical therapeutic field. The future use of chemically defined culture-media will certainly facilitate secretome production according to Good Manufacturing Practice (GMP) standards.